2008
DOI: 10.1061/(asce)1090-0241(2008)134:11(1655)
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Analysis of Cover Systems in Municipal Solid Waste Landfills

Abstract: Cover temperature variations were determined at four municipal solid waste landfills located in different climatic regions in North America: Michigan, New Mexico, Alaska, and British Columbia. Cover temperatures varied seasonally similarly to air temperatures and demonstrated amplitude decrement and phase lag with depth. Elevated temperatures in the underlying wastes resulted in warmer temperatures and low frost penetration in the covers compared to surrounding subgrade soils. The ranges of measured temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…As an exception, Koerner �2001� re ported high short-term waste temperatures �30°C over initial two years� followed by low long-term temperatures �10-20°C over 9.5 years�. For covers, Yeşiller et al �2008� reported that tempera tures typically followed seasonal trends with phase lag and am plitude decrement with depth. For bottom liner systems and bases of landfills, long-term temperatures between approximately 30 and over 50°C were observed.…”
Section: Introductionmentioning
confidence: 99%
“…As an exception, Koerner �2001� re ported high short-term waste temperatures �30°C over initial two years� followed by low long-term temperatures �10-20°C over 9.5 years�. For covers, Yeşiller et al �2008� reported that tempera tures typically followed seasonal trends with phase lag and am plitude decrement with depth. For bottom liner systems and bases of landfills, long-term temperatures between approximately 30 and over 50°C were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature ranges within the top 1 m of cover soils and in the geosynthetics in final covers beneath 1 m of cover soil are generally similar to temperature ranges the air above a landfill, with some reduction in seasonal temperature amplitude. In areas with cold winters and mild summers, geosynthetic temperatures in final covers have been reported from a maximum of 22-25°C to a minimum of 2-4°C (Yesiller et al 2008). …”
Section: Overburden Testsmentioning
confidence: 99%
“…The disposal of waste into landfill is the most commonly adopted method in many countries, despite being the least recommended waste management solution. Waste decomposition is always associated with the production of landfill gas (LFG) and leachate from the waste mass, and is accompanied by effects of heat generation as a result of the continuous aerobic and anaerobic processes (Yesiller et al, 2005(Yesiller et al, , 2008. Long-term heat generation in landfill is mainly caused by an LFG that primarily consists of methane and carbon dioxide due to the continuous biochemical process that primarily involves decomposition of organic waste components (Nastev et al, 2001;Yesiller et al, 2005).…”
Section: Introductionmentioning
confidence: 99%